Tangent Method and Some Dynamical Properties of an Oval-Like Billiard - Costa, Diogo Ricardo da [UNESP]; Hansen, Matheus; Silva, Mario Roberto [UNESP]; Leonel, Edson D. [UNESP] (World Scientific Publ Co Pte Ltd, 2022)
In this paper, we consider the evolution of an ensemble of noninteracting classical particles confined in a closed region. Each one of these particles experiences several elastic collisions with a rigid-smooth oval-like boundary. As known in the literature, numerical simulations for this kind of system demand too much time, mostly because of the time spent in solving transcendental equations. To deal with that, we highlight an alternative approach to speed up the search of solutions for the transcendental equations via the tangent method, which has proved to be a faster way to solve this problem when compared with other methods, like the bisection one. The methods applied here are generic and can be used or adapted for other billiard boundaries.
Keywords: Chaos; nonlinear dynamics; billiard; numerical method